2004
DOI: 10.1182/blood-2004-03-1066
|View full text |Cite
|
Sign up to set email alerts
|

A GTPase-activating protein binds STAT3 and is required for IL-6–induced STAT3 activation and for differentiation of a leukemic cell line

Abstract: IntroductionThe signal transducer and activator of transcription (STAT) family members STAT1-4, STAT5A, STAT5B, and STAT6 are activated through phosphorylation by the Janus kinase (JAK) family upon cytokine stimulation. The phosphorylated STATs form homodimers or heterodimers and translocate into the nucleus, where they regulate expression of their target genes. [1][2][3][4] Among them, STAT3 is activated mainly by the interleukin-6 (IL-6) family cytokines including IL-6, oncostatin M, and leukemia inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 59 publications
1
45
0
1
Order By: Relevance
“…In contrast, some studies suggest that RacGAP1 is able to mediate some of its functions independently of its GAP activity (38). Recently, RacGAP1 has also been implicated in regulating the localization and transcriptional activity of signal transducer and activation of transcription (STAT) proteins (39,40), a family of proteins that have been strongly implicated in the stromal decidualization response and embryo implantation (41). Here, we have shown that hESC Rac-GAP1 levels are down-regulated in response to human embryos and that this correlates with an increase in Rac1 activity observed in hESCs.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, some studies suggest that RacGAP1 is able to mediate some of its functions independently of its GAP activity (38). Recently, RacGAP1 has also been implicated in regulating the localization and transcriptional activity of signal transducer and activation of transcription (STAT) proteins (39,40), a family of proteins that have been strongly implicated in the stromal decidualization response and embryo implantation (41). Here, we have shown that hESC Rac-GAP1 levels are down-regulated in response to human embryos and that this correlates with an increase in Rac1 activity observed in hESCs.…”
Section: Discussionmentioning
confidence: 95%
“…The function of the nuclear Rac1, however, is still not understood. While STAT3 requires facilitated import into the nucleus via importin ␣ 5 (27), molecules other than importins, such as Rac1, are specifically required for the nuclear translocation of STAT3 (46). Kawashima et al (21) show that activated Rac1 is specifically required for the interaction of phospho-STAT5A with importins.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have previously determined that STAT3 activation is directly regulated by the small GTPase Rac1 in fibroblasts (44). Recent studies by us and others have shown that Rac1 contributes to maximal STAT3 activation, transcriptional activity, and nuclear translocation and that the STAT3/Rac1 interaction is important in STAT3 function (21,36,37,44,46,47). However, the results regarding the direct regulation of STAT3 by Rac1 have been somewhat contradictory, likely due to the fact that the studies have used different cell types and stimuli, and have often relied on overexpression studies using dominant negative forms of Rac1 (DnRac1).…”
Section: Discussionmentioning
confidence: 99%
“…These siRNA duplexes were manufactured and supplied by Dharmacon. Transfection was done with Lipofectamine 2000 (Invitrogen) as described previously (55). At 72 h after transfection, the cells were counted and subjected to Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%